The Role of Light in Enhancing the Nutritional and Antioxidant Qualities of Basil, Mint and Lemon Balm - Karolina Jakubczyk; Kinga Szymczykowska; Klaudia Melkis; Dominika Maciejewska-Markiewicz; Anna Nowak; Anna Muzykiewicz-Szymańska; Karolina Skonieczna-Żydecka (Foods)
Mint (Mentha L.), basil, (Ocimum basilicum) and Melissa (Melissa officinalis L.) are herbaceous plants from the Lamiaceae family. They have a wide range of health benefits and flavour properties which are highly valued around the world. Alternative methods of growing plants to minimise greenhouse gas emissions during autumn and winter are being sought in the face of increasing climate change. One way to achieve this is to switch from HPS to LED lighting. LED lighting has a longer lifespan and higher efficiency while using less energy and better matching the colour of the light to the needs of the herbs. This study tested the hypothesis that the type of illumination (solar, HPS, and LED) significantly impacts the antioxidant and nutritional qualities of herbs. The results indicated that LED lighting enhanced biochemical properties, supporting its adoption for sustainable plant cultivation.